Ospa wietrzna powikłana posocznicą i ropnym zapaleniem tkanek miękkich u 5-letniego chłopca - opis przypadku - Małecki, Paweł; Mania, Anna; Krasiński, Zbigniew; Harasymczuk, Jerzy; Jończyk-Potoczna, Katarzyna; Mazur, Katarzyna; Kemnitz, Paweł; Służewski, Wojciech; Figlerowicz, Magdalena (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Chickenpox is one of the most common childhood infectious diseases. Bacterial superinfections of the skin are the most common complications occuring in the disease. A 5-year-old boy was admitted to hospital owing to varicella-zoster virus infection complicated by purulent infection of the skin and subcutaneous tissue of the right leg. Before admission, symptomatic treatment and improper care of skin lesions were administered. During the inpatient stay, bacteriemia caused by Streptococcus pyogenes and venous thrombosis was diagnosed. Initially conservative treatment and targeted antibiotic therapy were implemented, and then the patient underwent surgery involving decompression of the muscle compartments and evacuation of abscesses. Following this procedure, his general condition improved considerably. Routine vaccination against chickenpox and proper skin care methods should be a standard of care as preventive measures of complications.